Wastewater-Based Epidemiology (WBE) Studies for Monitoring of Covid-19 Spread - KOCAMEMİ, BİLGE; ERKEN, ESRA (Springer International Publishing, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) started in Wuhan, China, in December 2019 and was announced as a worldwide pandemic spread by WHO on March 11, 2020. The countries have started to monitor surveillance of SARS-CoV-2 through medical tests. However, people with no or very light symptoms are usually not medically tested or never hospitalized, and their test results missed. In March 2020, it was recognized that the urine and feces of all infected people contain SARS-CoV-2. After that, wastewater-based epidemiology studies have gained significant importance around the world. This chapter aims to describe the basics of wastewater-based epidemiology (WBE) studies, the current situation in the world together with the post-Covid-19 approaches. Additionally, the major challenges in Covid-19 WBE studies are discussed.